Three years of follow-up of otodental syndrome in 3-year-old Chinese boy: a rare case report - Ji-mei Su; Su-juan Zeng; Xiao-wei Ye; Zhi-fang Wu; Xin-wen Huang; Janak L. Pathak (BMC, 2019)
Abstract Background Otodental syndrome is an exceptionally rare autosomal dominant condition characterized by a delayed eruption of posterior teeth, globodontia, lisping, and sensorineural hearing loss. In this case report, we reported a 3-year-old Chinese boy with the otodental syndrome. Case presentation A 3-year-old Chinese boy was referred to our hospital with complaint of no eruption of primary canines and molars. Three years follow-up showed lately erupted bulbous primary canines with hypoplastic enamel spot, globe-shaped primary molars and sensorineural hearing loss at 4 and a half-year-old age. We diagnosed otodental syndrome in the patient's mother with hearing loss at 16-year-old age. Gene sequencing and analysis of deafness-related genes GJB2, GJB3, SLC26A4, and mtDNA did not reveal any mutation or SNPs in the patient and his mother. Conclusions This case report highlights the importance of detailed medical, dental, and family history examination, as well as multi-disciplinary teamwork for diagnosis and treatment of otodental syndrome.